How democracies live: a review essay on Shadi Hamid’s The Problem of Democracy - Murtazashvili, Ilia (Frontiers in Political Science, 2024)
Shadi Hamid’s The Problem of Democracy is the rare book that will be of immense value to both those who agree and disagree with its argument. This essay constructively considers Hamid’s arguments. It suggests that the case for democratic minimalism might be strengthened by considering the role of economic freedom as a source of democratic resilience.